Cooperatives, contract farming, and farm size: The case of tomato producers in Nepal. Issue 4 (28th May 2018) - Mishra, Ashok K.; Kumar, Anjani; Joshi, Pramod K.; D'Souza, Alwin
Abstract: This study investigates the impact of contract farming (CF) through cooperatives in tomatoes on employment and economic performance of smallholders in a low‐income developing country. Using farm‐level data from Nepal and a nonparametric matching estimator, the study finds a negative and significant effect of CF on employment. However, CF through cooperatives has a positive and significant impact on profits, and yield. We find that small farms (≤0.51 ha) with contracts tend to gain in profits and yield per hectare. However, large farms (>0.85 ha) with contracts employ significantly less hired labor per hectare. Finally, our estimates reveal that, compared to independent producers, smallholder households in Nepal that engaged in CF with both input and output conditions received, on average, higher profits and yield. Findings underscore the importance of cooperatives and CF. [EconLit citations: C31, D23, Q12, Q13]